Imaging of Lesser Metatarsophalangeal Joint Plantar Plate Degeneration, Tear, and Repair - Linklater, James M.; Bird, Stephen J. (Seminars in Musculoskeletal Radiology, 2016)
Plantar plate degeneration and tear is a common cause of forefoot pain, typically involving the second metatarsophalangeal joint at the proximal phalangeal insertion laterally, frequently confused with the second web space Morton neuroma. The condition has received increased attention with the development of surgical techniques that can result in successful repair of the plantar plate and substantial improvement in patient symptoms. High-resolution MRI or ultrasound can confirm a diagnosis of plantar plate degeneration and tear and exclude other pathologies, particularly Morton neuroma. The normal plantar plate is a mildly hyperechoic structure on ultrasound and is hypointense on all conventional MR sequences. Plantar plate degeneration manifests on ultrasound as hypoechoic echotextural change and on MRI as mild signal hyperintensity on short TE sequences, becoming less conspicuous on long TE sequences. Adjacent entheseal bony irregularity is commonly present. Plantar plate tears on ultrasound may be seen as an anechoic cleft defect or area of heterogeneous echotexture, sometimes more conspicuous with dorsiflexion stress. Plantar plate tears demonstrate greater signal hyperintensity on proton-density sequences, becoming more conspicuous on fat-suppressed proton density and T2-weighted sequences. Edema and fibrotic change in the pericapsular fat plane is commonly seen in the setting of an adjacent plantar plate tear and should not be misinterpreted as reflecting a Morton neuroma.
Keywords: plantar plate; forefoot; ultrasound; MRI; metatarsalgia